Au thin films nano-structuration on polycrystalline anatase and rutile TiO2 substrates towards photocatalytic applications. (February 2016) - Cacciato, G.; Ruffino, F.; Zimbone, M.; Reitano, R.; Privitera, V.; Grimaldi, M.G.
Abstract: Recent years have shown a renewed interest in the use of functional semiconductors for conversion of solar to chemical energy by photocatalysis. Moreover, metal nanoparticles (NPs) are able to improve the photocatalytic efficiency due to their localized surface plasmon resonance (LSPR). In this sense, Au NPs are of particular interest since they exhibit resonant behavior in the visible range, allowing the harvesting of a large amount of the solar flux. Among semiconductor photocatalysts, TiO2 has been investigated due to its abundance, stability, non-toxicity and high photocatalytic activity. In this work, the properties of Au NPs/TiO2 composite materials are investigated in detail due to their potential application in visible driven photocatalysis. Au NPs are obtained after thermal dewetting of sputtered Au films on TiO2 . We correlate the photocatalytic activity of the Au NPs-TiO2 composite film under UV illumination with structural properties and TiO2 phase.